Dampak Pandemi bagi Global Value Chain Industri Kakao Indonesia - Hasna Wijayati (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
The contribution of the cocoa industry to the Indonesian economy is very large. However, the Indonesian cocoa industry is heavily dependent on the global cocoa industry, due to its position in the Global Value Chain. The majority of cocoa products destined for the global market are produced by smallholders who are limited in the implementation of Good Corporate Governance. The presence of a pandemic and these limitations presents a multidimensional crisis and threatens the position of the Indonesian cocoa industry. The study analyzes the impact of the pandemic on the GVC of the Indonesian cocoa industry, by relating it to the limitations of the implementation of GCG in the cocoa industry. The research method is descriptive qualitative with a document study approach. The main theory used is GVC. The results showed that the pandemic era had many impact on various aspects of the cocoa industry, one of which was also related to the limitations of GCG implementations. The impact including price channels, supply channels and financial channels. In these three networks, Indonesia experienced several declines, such as the value of exports, although they did not occur significantly.